Oxaliplatin-induced peripheral neurotoxicity in colorectal cancer patients: mechanisms, pharmacokinetics and strategies - Cheng, Fang; Zhang, Ruoqi; Sun, Chen; Ran, Qian; Zhang, Cuihan; Shen, Changhong; Yao, Ziqing; Wang, Miao; Song, Lin; Peng, Cheng (Frontiers in Pharmacology, 2023)
Oxaliplatin-based chemotherapy is a standard treatment approach for colorectal cancer (CRC). However, oxaliplatin-induced peripheral neurotoxicity (OIPN) is a severe dose-limiting clinical problem that might lead to treatment interruption. This neuropathy may be reversible after treatment discontinuation. Its complicated mechanisms are related to DNA damage, dysfunction of voltage-gated ions channels, neuroinflammation, transporters, oxidative stress, and mitochondrial dysfunction, etc. Several strategies have been proposed to diminish OIPN without compromising the efficacy of adjuvant therapy, namely combination with chemoprotectants (such as glutathione, Ca/Mg, ibudilast, duloxetine, etc.), chronomodulated infusion, dose reduction, reintroduction of oxaliplatin and topical administration [hepatic arterial infusion chemotherapy (HAIC), pressurized intraperitoneal aerosol chemotherapy (PIPAC), and hyperthermic intraperitoneal chemotherapy (HIPEC)]. This article provides recent updates related to the potential mechanisms, therapeutic strategies in treatment of OIPN, and pharmacokinetics of several methods of oxaliplatin administration in clinical trials.